Influence of Hashimoto thyroiditis on diagnosis and treatment of thyroid nodules - Mao, Linfeng; Zheng, Chunmei; Ou, Shengzhao; He, Youwu; Liao, Chuanjie; Deng, Ganlu (Frontiers in Endocrinology, 2022)
Background: As the prevalence of Hashimoto's thyroiditis(HT) and thyroid cancer(TC) has been increasing dramatically in recent years, the association between the two diseases has been widely debated and studied. However, no consistent findings are available and the relationship remains controversial. In this study, we analyzed the influence of Hashimoto thyroiditis on the diagnosis and treatment of thyroid nodules and investigated the relationship between HT and TC. Methods: From Jan 2017 to Apr 2021, 4678 patients underwent thyroid surgery were collected. Of these patients, 440 were diagnosed with HT (242 nodular goiter(NG) with HT, 198 TC with HT). These patients were grouped when appropriate and the data from these patients were statistically analyzed by using SPSS and GraphPad Prism 6. Results: HT occurred in 198 of 1089 (18.2%) TC patients and 242 of 3589 (6.74%) patients without TC (p=0.000). In terms of the ultrasonography features, in the NG with HT group, 34.7% (84/242) of patients had fine calcification and 45.9% (111/242) of patients whose TI-RADS classification were > Level 3. In the isolated PTC group, 32.3% (2343/7260) LN were metastasis-positive while in the NG with HT group, only 26% (504/1939) LN were metastasis-positive (P=0.000). The proportion of PTMC was significantly higher (P=0.000), while the proportion of multifocal carcinoma was significantly lower when coexisting with HT (P=0.029). When comparing the data from the two groups diagnosed as PTMC coexisting with HT or not, there was no significant difference in the composition ratio of tumor number, LN metastasis, LN dissection area, regional LN metastasis and number of negative/positive LN (P=0.614, P=0.051, P=0.139, P=0.350, P=1.000 and P=0.333 respectively). In the MPTC group, 57.7% (1193/2063) LN were metastasis-positive while in the MPTC with HT group, only 23.6% (50/212) LN were metastasis-positive (P=0.000). Conclusions: Our data suggested that HT is associated with an increased risk of developing TC but may be a protective factor against PTC progression and metastasis. The coexistence of HT affects the judgment of thyroid nodules by ultrasonography.